Factors Affecting Gestation Length in Gir Cattle - Parikh, Suryakant S.; Savaliya, Bhagvanji D.; Patbandha, Tapas K.; Makwana, Rinkesh B.; Gamit, Pranav M.; Parmar, Monika R. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present study was planned to understand the factors affecting gestation length in nulliparous and pluriparous Gir cows. A cumulative ten years (2010-2019) full term calving record (n = 1272) of Gir cows were incorporated. The overall mean gestation length of Gir cattle was 283.29 ± 0.16 days. It was shortest in 8th and above parities and longest in 7th parity Gir cows (282.39 and 285.84 days, respectively); with statistically significant (p
Keywords: Gestation length; Gir cattle; Month of service; Sex of calf; Parity; Period